Adopting better corporate governance: Evidence from cross-border mergers - Bris, Arturo; Brisley, Neil; Cabolis, Christos (Journal of Corporate Finance, 2008)
Cross-border mergers allow firms to alter the level of protection they provide to their investors, because target firms usually import the corporate governance system of the acquiring company by law. Therefore, cross-border mergers provide a natural experiment to analyze the effects of changes in corporate governance on firm value, and on an industry as a whole. We construct measures of the change in investor protection induced by cross-border mergers in a sample of 7330 ‘national industry years’ (spanning 39 industries in 41 countries in the period 1990–2001. We find that the Tobin's Q of an industry — including its unmerged firms — increases when firms within that industry are acquired by foreign firms coming from countries with better shareholder protection and better accounting standards. We present evidence that the transfer of corporate governance practices through cross-border mergers is Pareto improving. Firms that can adopt better practices willingly do so, and the market assigns more value to better protection.